The Practicality of Popular Scientific Books based on the Diversity of Tree Species on the Puting Riverbank - Kristina Febriana Panjaitan; Muhammad Zaini; Danang Biyatmoko (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2021)
Learning resources using popular scientific books based on local potential found in an area is one solution that can be used to overcome problems in learning Plant Ecology courses. This development research aims to describe the practicality of the contents, expectations and actual prototypes of a popular scientific book entitled “Tree Species Diversity in Puting Riverbank”. The research method uses a Tessmer design that focuses on formative evaluation. The results of the research on the practicality test of the content seen from the readability results of students got an average value of 94.23% with very good criteria, while the results of the practicality test of expectations and actual seen from the results of the implementation of popular scientific books which obtained an average value of 88.89% with very good criteria and the results of student responses to popular scientific books with an average of 95.96% with criteria strongly agree. This shows that a popular scientific book with the title "Diversity of Tree Species on the Puting Riverbank" is very practical to use to explore students' critical thinking skills in learning plant ecology.AbstrakSumber belajar menggunakan buku ilmiah populer berbasis potensi lokal yang terdapat pada suatu daerah merupakan salah satu solusi yang dapat digunakan untuk mengatasi masalah di dalam pembelajaran mata kuliah Ekologi Tumbuhan. Penelitian pengembangan ini bertujuan untuk mendeskripsikan kepraktisan isi, harapan dan aktual prototipe buku ilmiah populer yang berjudul “Keanekaragaman Jenis Pohon di Bantaran Sungai Puting” Metode penelitian menggunakan desain Tessmer yang berfokus pada evaluasi formatif. Hasil penelitian pada uji kepraktisan isi yang dilihat dari hasil keterbacaan mahasiswa mendapatkan nilai rata-rata 94,23% dengan kriteria sangat baik, sedangkan hasil uji kepraktisan harapan dan aktual dilihat dari hasil uji keterlaksanaan buku ilmiah populer yang memperoleh nilai rata-rata 88.89% dengan kriteria sangat baik dan hasil respon mahasiswa terhadap buku ilmiah populer dengan rata-rata 95,96% dengan kriteria sangat setuju. Hal tersebut menunjukan bahwa buku ilmiah populer dengan judul “Keanekaragaman Jenis Pohon di Bantaran Sungai Puting” sangat praktis digunakan untuk menggali keterampilan berpikir kritis mahasiswa dalam pembelajaran Ekologi Tumbuhan.